BIOCHEMICAL ALTERATIONS DUE TO COMBINED METHANOLIC EXTRACT OF DALBERGIA SISSOO AND AZADIRACHTA INDICA ON LIVER AND KIDNEY OF SPRAGUE DAWLEY RATS - RAYEES AHMAD; VINITA AHIRWAR; KUSUM SINGH (International Journal of Pharma and Bio Sciences, 2014)
Dalbergia sissoo and Azadirachta indica are commonly known trees of India. They belong to family leguminoseae (fabaceae) and meliaceae respectively. They are broadly used in folk medicine for several diseases. The present study is carried out on biochemical parameters i.e. on content of protein and glycogen with standardized method in liver and kidney of Sprague-dawley rats. Due to combined extract of these two plants at single and daily doses of 250 mg/kg b.wt. results revealed significantly decreased (P ≤ 0.05) content of both protein and glycogen as compared to their respective control groups.